Optical measurement of an impact reaction in a modeled wing - Saldaña-Heredia, Alonso; Martínez-Calzada, Víctor; Del Villar-Ramírez, Víctor Uriel; Rodríguez-Torres, Adriana (Frontiers in Physics, 2022)
In this research, an impact reaction which was provoked far from its origins was studied. A metal box filled with sand was used to emulate a rigid body in which a steel bar was embedded; these conditions simulated the fuselage and wing, respectively, and the impact was applied to the rigid body and the measurement to the bar. For this, an optical technique was used to measure the relative displacement of the steel bar, and the measurements are obtained by applying digital image correlation; 2D images were obtained from the speckles generated as a reflection of the beam on the material. The results were studied through the modified Gauss–Newton analytical approach obtaining a maximum standard error deviation of 0.144 from the experimental results.